An unusual case of self-induced electrolyte depletion. Issue 4 (April 1971) - Love, D. R.; Brown, J. J.; Fraser, R.; Lever, A. F.; Robertson, J. I. S.; Timbury, G. C.; Thomson, Sheena; Tree, M.
Abstract : A case of anorexia nervosa, presenting with unexplained hypokalaemia, is described. The patient was also secretly addicted to purgatives and diuretics. During an attempted metabolic balance study she secretly disposed of food and excreta, which were smuggled from the hospital by her sister. The patient induced her husband to bring his own stools into the ward, these then being substituted for her own. The interrelationships of the electrolyte disturbances, elevation of plasma renin, renin substrate, and hyperaldosteronism are discussed, particularly in connexion with the pathogenesis of peripheral oedema in anorexia nervosa.